At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Step-by-step explanation:
-5x+5y=15(multiply by 2)
3×-2y=-8(multiply by 5)
-10×+10y=30
15×-10y=-40
5x=-10
x=-2
Here,
-5x+5y=15.......(I)
and
3x-2y=8.....(II)
Now,
adding 3 in eqn (II)
so, 6x-5y=8
Now,
combining eqn (I) &(II)
-5x+5y=15
+6x-5y=8
[both 5y is cancelled ]
or, x=7
Now,
in eqn(i)
-5x+5y=15
or, -5*7+5y=15
or, -35+5y=15
or, -35-15=-5y
or, -50=-5y
or, -50/-5=y
[minus is cancelled ]
Therefore, y=10 and x=7
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.